Catalyst for acetylene hydrochlorination reaction and preparation method thereof
The clamp-shaped structure is constructed through the coordinated coordination of copper and phosphorus, and the stability and cost problems of gold-based catalysts in the acetylene hydrochlorination reaction are solved, and the catalytic effects of low gold loading, high activity and high stability are achieved.
Patent Information
- Application Number
- CN202510319050.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-07-08
AI Technical Summary
Existing gold-based catalysts have problems such as insufficient stability, serious carbon deposits and high cost in the acetylene hydrochlorination reaction, which are difficult to promote and apply on industrial scale.
By introducing the coordinated coordination between copper and phosphorus, a clamp-shaped structure is constructed, electron oscillation regulation of gold sites is achieved, and a low-gold-loaded catalyst is prepared to inhibit gold aggregation and carbon accumulation.
It improves the activity and stability of the catalyst, reduces the cost of industrial application, and realizes efficient acetylene hydrochlorination reaction.
Smart Images

Figure CN120268426A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts and their preparation in chemical production, and particularly relates to a catalyst for acetylene hydrochlorination and a preparation method thereof. Background Art
[0002] Polyvinyl chloride (PVC) is one of the most widely produced general plastics globally and is widely used in fields such as construction, packaging, electronics, and appliances. According to statistics, the global PVC production capacity exceeded 60 million tons in 2020, with a market scale reaching tens of billions of dollars. The industrial production of PVC takes the polymerization of vinyl chloride monomer (VCM) as the core process, and VCM is mainly prepared by the acetylene hydrochlorination method or the ethylene oxychlorination method. However, the mercury catalysts used in traditional processes pose environmental pollution risks and are contrary to the global trend of green chemistry development. With the increasingly strict environmental protection regulations and the higher requirements for sustainable development, the development of an environmentally friendly PVC production process has become a key issue that the industry urgently needs to solve and is of great significance for promoting the green transformation of the entire industrial chain.
[0003] Currently, the research and development of environmentally friendly mercury-free catalysts have become an important research direction. As a key link in PVC production, the industrial production of vinyl chloride monomer (VCM) generally uses a mercury chloride (HgCl2) catalyst system supported on activated carbon (AC). However, this technology has significant mercury consumption and environmental pollution problems, which have attracted widespread attention globally. To address this challenge, scientific researchers are committed to developing efficient mercury-free alternative catalysts, among which gold-based catalysts show significant industrial application prospects. However, studies have shown that gold-based catalysts have problems with insufficient stability in the acetylene hydrochlorination reaction system, mainly manifested as reduction phenomena and carbon deposition effects during the catalytic process. In addition, their relatively high preparation cost also restricts the promotion and application of this catalyst on an industrial scale to a certain extent.
[0004] The defects and deficiencies of the prior art mainly focus on the following points:
[0005] a) Gold particles are prone to aggregation: The oxidation-reduction of Au(I) / Au(III) in the reaction is uncontrollable, resulting in the sintering inactivation of gold nanoparticles. b) Severe carbon deposition: Acetylene reacts excessively with high-valent gold to form carbon deposits, covering the active sites. c) High cost: A high gold loading (>1 wt.%) limits industrial applications. Therefore, the development of gold catalysts with low loading, high activity, and high stability has become an extremely urgent need in the industry. Summary of the Invention
[0006] The prior art regulates the electronic state of gold through a single electron donor (such as a ligand) or acceptor (such as a metal additive), but it is unable to achieve dynamic equilibrium and is difficult to balance activity and stability. To solve the above problems existing in the prior art, the present invention provides a catalyst for acetylene hydrochlorination and a preparation method thereof. By introducing copper (Cu) and phosphorus (P) for coordinated bonding to construct a pincer structure, the electronic oscillation regulation of gold sites is realized, significantly improving the catalytic performance, in order to at least partially solve the above technical problems.
[0007] In a first aspect, the present invention provides a catalyst, which includes an active component, and the active component includes Au, Cu, and P; wherein, Au atoms are located at the (pincer-type) coordination center formed by Cu atoms and P atoms. In the present invention, the P ligand is preferably iPr2PCl (diisopropylphosphine chloride), and this ligand is the active component of the catalyst provided by the present invention.
[0008] Preferably, the weight percentage (loading amount) of Au is 0.1% - 0.2% (for example, it can be 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2% or all values within the range. Due to space limitations, they will not be elaborated here), the molar ratio of Cu to Au is (0 - 30):1 (for example, it can be 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, 29:1, 30:1 or all values within the range. Due to space limitations, they will not be elaborated here), and the molar ratio of P to Au is (0 - 20):1 (for example, it can be 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 20:1 or all values within the range. Due to space limitations, they will not be elaborated here).
[0009] Preferably, the catalyst further includes a catalyst carrier, and the catalyst carrier includes activated carbon (AC).
[0010] In a second aspect, the present invention provides a preparation method of the catalyst according to the first aspect, including the following steps:
[0011] Step 1: Dissolve HAuCl4, CuCl2, and iPr2PCl in isopropanol to form a precursor solution;
[0012] Step 2: Immerse the precursor solution in the activated carbon carrier and let it stand;
[0013] Step 3: Dry at a temperature of 120 - 150°C (the temperature can be, for example, 120°C, 122°C, 124°C, 126°C, 128°C, 130°C, 132°C, 134°C, 136°C, 138°C, 140°C, 142°C, 144°C, 146°C, 148°C, 150°C or all values within the range; due to space limitations, they will not be elaborated further), to obtain the catalyst.
[0014] Preferably, the temperature for standing still in Step 2 is 70 - 80°C (the temperature can be, for example, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C or all values within the range; due to space limitations, they will not be elaborated further), and the time is 2 - 4 h (for example, it can be 2 h, 2.5 h, 3 h, 3.5 h, 4 h or all values within the range; due to space limitations, they will not be elaborated further).
[0015] Preferably, the drying time in Step 3 is 6 - 12 h, for example, it can be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h or all values within the range; due to space limitations, they will not be elaborated further.
[0016] Preferably, the method for preparing the catalyst includes the following steps:
[0017] Step 1: Dissolve HAuCl4, CuCl2 and iPr2PCl in isopropanol to form a precursor solution;
[0018] Step 2: Immerse the precursor solution in an activated carbon support and stand still at 70 - 80°C for 2 - 4 h;
[0019] Step 3: Dry at a temperature of 120 - 150°C for 6 - 12 h to obtain the catalyst.
[0020] In a third aspect, the present invention provides a method for acetylene hydrochlorination reaction, including the following steps:
[0021] Contact a raw material containing acetylene and hydrogen chloride with a catalyst and react to prepare vinyl chloride;
[0022] The catalyst is selected from at least one of the catalysts described in the first aspect and the catalysts prepared by the preparation method described in the second aspect.
[0023] Preferably, the acetylene space velocity of the reaction is 300 - 1080 h -1 (for example, it can be 300 h -1 , 400 h -1 , 500 h -1 , 600 h -1 , 700 h -1 , 800 h -1, 900 h -1 , 1000 h -1 , 1080 h -1 or all values within the said range, which will not be elaborated here due to space limitations), the reaction temperature is 160 - 200 °C (for example, it can be 160 °C, 165 °C, 170 °C, 175 °C, 180 °C, 185 °C, 190 °C, 195 °C, 200 °C or all values within the said range, which will not be elaborated here due to space limitations).
[0024] Preferably, the volume ratio of hydrogen chloride to acetylene in the raw materials is (1.1 - 1.3):1. For example, it can be 1.1:1, 1.12:1, 1.14:1, 1.16:1, 1.18:1, 1.20:1, 1.22:1, 1.24:1, 1.26:1, 1.28:1, 1.30:1 or all values within the said range, which will not be elaborated here due to space limitations).
[0025] Compared with the prior art, the present invention has at least the following beneficial effects:
[0026] The present invention provides a catalyst for acetylene hydrochlorination and a preparation method thereof. The catalyst is a low-gold-loading, high-activity, and high-stability acetylene hydrochlorination catalyst. By the synergistic coordination of copper and phosphorus, the electronic state of gold is regulated, the aggregation of gold and carbon deposition are inhibited, and the industrial application cost is reduced.
[0027] Microscopically, the catalyst provided by the present invention constructs a (pincer-type) coordination center structure at the Au site. Electrons oscillate rapidly in the structure during the catalytic process to complete efficient catalysis. This electron oscillation can rapidly modulate the electron density of the Au site, meet the different requirements for the stepwise adsorption and catalysis of acetylene and hydrogen chloride, and directly achieve an ultra-low load of Au and a huge improvement in catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 are the comparison of acetylene conversion rate and the comparison of VCM selectivity; among them, the comparison of acetylene conversion rate (1a) and the comparison of VCM selectivity (1b) of the catalyst AuCux / AC (with different x values);
[0029] Catalyst AuCu 24 Px / AC (with different x values) for the comparison of acetylene conversion rate (1c) and the comparison of VCM selectivity (1d);
[0030] Catalyst AuCu 24 / AC for the comparison of acetylene conversion rate (1e) and the comparison of VCM selectivity (1f) with different organic ligands;
[0031] (Comparative Tests 1-3) Tests on acetylene conversion rate (1g) and VCM selectivity (1h) of the catalyst prepared in Example 1 at different C2H2 space velocities.
[0032] Figure 2 It is the comparison of acetylene conversion rate between different component combinations of the catalyst (2a); the comparison of acetylene conversion rate / VCM selectivity between different component combinations of the catalyst (2b).
[0033] Figure 3 It is the thermogravimetric comparison of the catalyst before and after the reaction, where the Au / AC catalyst (3a), AuCu 24 / AC catalyst (3b), AuCu 24 P 16 / AC catalyst (3c).
[0034] Figure 4 It is the morphological structure diagram of the catalyst before and after the reaction, where the TEM of the Au / AC catalyst before (4a) and after (4b) the reaction; the SAED pattern of the Au / AC catalyst after the reaction (4c); the energy-dispersive X-ray spectra of the Au / AC catalyst before (4d, 4e) and after (4f, 4g) the reaction; AuCu 24 / AC catalyst before (4h) and after (4i) the reaction; the SAED pattern of the AuCu 24 / AC catalyst after the reaction (4j); the energy-dispersive X-ray spectra of the AuCu 24 / AC catalyst before (4k, 4l, 4m) and after (4n, 4o, 4p) the reaction.
[0035] Figure 5 It is the 24 P 16 TEM and energy-dispersive X-ray spectra of the AuCu
[0036] Figure 6 Among different catalyst components 31 P nuclear magnetic resonance spectrogram ( 31 P NMR). Detailed Implementation Modes
[0037] The prior art regulates the electronic state of Au through a single electron donor (such as a ligand) or acceptor (such as a metal additive), and it is impossible to achieve dynamic balance, and it is difficult to balance activity and stability. To solve the above problems existing in the prior art, the applicant has conducted intensive research and provided a catalyst for acetylene hydrochlorination and its preparation method. By introducing copper (Cu) and phosphorus (P) for coordinated coordination and constructing a pincer coordination center structure, the electronic oscillation regulation of the Au site is realized, and the catalytic performance is significantly improved.
[0038] Specifically, the present invention provides a catalyst, which comprises an active component, and the active component comprises Au, Cu and P; wherein, Au atoms are located at the (pincer-type) coordination center formed by Cu atoms and P atoms. In the present invention, the P ligand is preferably iPr2PCl (diisopropylphosphine chloride), and this ligand is the active component of the catalyst provided by the present invention.
[0039] As one of the preferred embodiments, the weight percentage (loading amount) of Au is 0.1% - 0.2% (for example, it can be 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2% or all values within the range, which will not be elaborated due to space limitations), the molar ratio of Cu to Au is (0 - 30):1 (for example, it can be 12:1, 14:1, 22:1, 16:1, 18:1, 20:1, 22:1, 24:1, 26:1, 28:1 or all values within the range, which will not be elaborated due to space limitations), and the molar ratio of P to Au is (0 - 20):1 (for example, it can be 8:1, 10:1, 12:1, 14:1, 16:1, 18:1, 20:1 or all values within the range, which will not be elaborated due to space limitations).
[0040] As one of the preferred embodiments, the catalyst further comprises a catalyst carrier, and the catalyst carrier comprises activated carbon (AC).
[0041] In the second aspect, the present invention provides a preparation method of the catalyst described in the first aspect, comprising the following steps:
[0042] Step 1: Dissolve HAuCl4, CuCl2 and iPr2PCl (diisopropylphosphine chloride) in isopropanol to form a precursor solution;
[0043] Step 2: Immerse the precursor solution in the activated carbon carrier and let it stand;
[0044] Step 3: Dry at a temperature of 120 - 150 °C (the temperature can be, for example, 120 °C, 122 °C, 124 °C, 126 °C, 128 °C, 130 °C, 132 °C, 134 °C, 136 °C, 138 °C, 140 °C, 142 °C, 144 °C, 146 °C, 148 °C, 150 °C or all values within the range, which will not be elaborated due to space limitations) to obtain the catalyst.
[0045] As one of the preferred embodiments, the temperature for standing still in step two is 70 - 80 °C (the temperature can be, for example, 70 °C, 71 °C, 72 °C, 73 °C, 74 °C, 75 °C, 76 °C, 77 °C, 78 °C, 79 °C, 80 °C or all values within the range, which will not be elaborated due to space limitations), and the time is 2 - 4 h (for example, it can be 2 h, 2.5 h, 3 h, 3.5 h, 4 h or all values within the range, which will not be elaborated due to space limitations).
[0046] As one of the preferred embodiments, the drying time in step three is 6 - 12 h, for example, it can be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h or all values within the range, which will not be elaborated due to space limitations).
[0047] As one of the preferred embodiments, the preparation method of the catalyst includes the following steps:
[0048] Step 1: Dissolve HAuCl4, CuCl2 and iPr2PCl in isopropanol to form a precursor solution;
[0049] Step 2: Immerse the precursor solution in an activated carbon carrier and stand still at 70 - 80 °C for 2 - 4 h;
[0050] Step 3: Dry at 120 - 150 °C for 6 - 12 h to obtain the catalyst.
[0051] In the third aspect, the present invention provides a method for the hydrochlorination reaction of acetylene, which includes the following steps:
[0052] Contact a raw material containing acetylene and hydrogen chloride with the catalyst and react to prepare vinyl chloride;
[0053] The catalyst is selected from at least one of the catalysts described in the first aspect and the catalysts prepared by the preparation method described in the second aspect.
[0054] As one of the preferred embodiments, the acetylene space velocity is 300 - 1080 h -1 (for example, it can be 300 h -1 、400 h -1 、500 h -1 、600 h -1 、700 h -1 、800 h -1 、900 h -1 、1000 h -1 、1080 h -1Or all values within the said range, which will not be elaborated here due to space limitations), the reaction temperature is 160 - 200 °C (for example, it can be 160 °C, 165 °C, 170 °C, 175 °C, 180 °C, 185 °C, 190 °C, 195 °C, 200 °C or all values within the said range, which will not be elaborated here due to space limitations).
[0055] As one of the preferred embodiments, the raw material volume ratio of hydrogen chloride to acetylene is (1.1 - 1.3):1. For example, it can be 1.1:1, 1.12:1, 1.14:1, 1.16:1, 1.18:1, 1.20:1, 1.22:1, 1.24:1, 1.26:1, 1.28:1, 1.30:1 or all values within the said range, which will not be elaborated here due to space limitations).
[0056] To make the objectives, technical solutions and advantages of the present invention clearer and more understandable, the present invention will be further described in detail below with reference to specific embodiments and the accompanying drawings.
[0057] Thermogravimetric analysis (TGA) was performed using a TG / DSC 2STARe system (METTLER TOLEDO, Switzerland). The sample was heated from 40 °C to 800 °C at a heating rate of 10 °C / min in an air atmosphere (flow rate 50 mL / min).
[0058] Transmission electron microscopy (TEM), elemental distribution imaging and selected area electron diffraction (SAED) tests were carried out using a JEOL JEM-F200 field emission transmission electron microscope (JEOL, Japan).
[0059] 31 31P nuclear magnetic resonance (NMR) was measured by an Avance NEO 600 spectrometer (Bruker, USA), and inductively coupled plasma optical emission spectrometry (ICP-OES) tests were completed using a 5110 instrument (Agilent, USA).
[0060] Example 1 Preparation of AuCu 24 P 16 / AC catalyst
[0061] Preparation of activated carbon before catalyst synthesis: Activated carbon (AC) was soaked in aqua regia at 80 °C for 2 h for acid treatment. Then it was rinsed with deionized water until neutral, and then dried in an oven at 150 °C to obtain the support material AC.
[0062] All catalysts used in this study were prepared by the incipient wetness impregnation method: AuCu 24 P 16Preparation of AuCu / AC: Using isopropanol as the solvent, add appropriate amounts of 0.06232 g of CuCl2, 0.0053 g of HAuCl4, and 0.0371 g of iPr2PCl (0.15 wt.% Au (calculated as Au), Cu / Au molar ratio of 24:1, P / Au molar ratio of 16:1). Stir for 0.5 h to completely disperse, and then slowly add 2.0 g of the AC prepared in the previous step. Seal the mixture with plastic wrap and place it in a water bath at 70 °C. After 6 hours, transfer the sample to an oven at 120 °C and dry it overnight to obtain the prepared catalyst AuCu 24 P 16 / AC.
[0063] By changing the amounts of CuCl2 and iPr2PCl, catalysts with different molar ratios were prepared. Among them, the batch samples with Au:Cu (molar ratio (12 - 28):1) and AuCu 24 :P (molar ratio 1:(8 - 20)) were determined. According to the above steps, replace iPr2PCl with other ligands to prepare catalysts with different ligands.
[0064] Example 2 Testing the acetylene conversion rate of catalysts with different component combinations
[0065] 1) Selection test of catalyst composition:
[0066] Test the catalyst prepared in Example 1 under the conditions of 180 °C and a C2H2 space velocity of 540 h -1 . As shown in Figure 1 a, 1b, the performance of the AuCu x / AC catalyst increases within a certain range as the proportion of Cu element increases, but the increasing rate tends to slow down. As Cu increases, the stability of the catalyst begins to decline. Considering the acetylene conversion rate and catalyst stability comprehensively, it is determined that the AuCu 24 / AC catalyst is the best catalyst among the AuCu x / AC catalysts. Under the above-mentioned catalytic conditions, the acetylene conversion rate of this catalyst is 94.52%, and the deactivation rate is 1.65% / h. Among them, the deactivation rate is calculated by subtracting the final reaction conversion rate from the highest reaction conversion rate within the reaction time (24 h), and then dividing by the reaction time, which can be obtained from the Figure 1 test results.
[0067] Introducing iPr2PCl into the catalytic system improves the stability of the catalyst. As shown in Figure 1 c, 1d, by adjusting the addition amount of iPr2PCl, the stability of the catalyst shows a trend of first increasing and then decreasing. Among them, AuCu 24 P 16 / AC has the highest catalytic performance and stability. AuCu 24P 16 The test results of the acetylene conversion rate of AuCu / AC are as follows: the acetylene conversion rate is 98.84%, and the deactivation rate is 0.078% / h.
[0068] At the optimal ratio, while referring to the regulatory effects of several other organic ligands: L1 is p-toluenesulfonyl chloride, L2 is tert-butyl hypochlorite, L3 is tetraethylammonium chloride, L4 is 1-ethyl-3-methylimidazolium chloride, and L5 is iPr2PCl. As Figure 1 shown in e and 1f, it can be seen that compared with the AuCu 24 / AC catalyst, the heteroatom ligands have greatly improved the stability of the catalyst, and iPr2PCl has the highest performance.
[0069] 2) Comparative test of catalyst composition:
[0070] As Figure 1 shown in g and 1h, Comparative test 1: Omit CuCl2, and the remaining preparation methods are the same as in Example 1. At 180 °C and a C2H2 space velocity of 540 h -1 conditions, the acetylene conversion rate was tested, and the results were as follows: the acetylene conversion rate was only 44.80%, and the deactivation rate was 0.045% / h.
[0071] Comparative test 2: Omit iPr2PCl, and the remaining preparation methods are the same as in Example 1. At 180 °C and a C2H2 space velocity of 540 h -1 conditions, the acetylene conversion rate was tested, and the results were as follows: the acetylene conversion rate was 94.52%, and the deactivation rate was 1.65% / h. After the reaction, the particles were significantly aggregated, and the carbon deposition reached 0.9 wt.%, indicating that its stability was poor and it was inferior to the catalyst of the present invention (see Example 3 for details).
[0072] Comparative test 3: Increase the C2H2 space velocity to 1080 h -1 Under the above conditions, the acetylene conversion rate of the catalyst prepared in Example 1 was tested, and the results were as follows: the deactivation rate increased significantly, reaching 0.26% / h.
[0073] Comparative tests 4 - 14: Table 1 shows the types of catalysts disclosed in the published literature and the main characteristic parameters of the acetylene hydrochlorination reaction process. It can be seen that the acetylene conversion rate of the catalyst prepared in Example 1 is higher than that of most of the disclosed acetylene hydrochlorination reaction catalysts, indicating that the catalyst provided by the present invention has high performance for the hydrochlorination reaction. Compared with traditional multi-metal catalysts and metal-ligand catalysts, AuCu 24 P 16 / AC combines the advantages of both types of catalysts and has high catalytic stability and acetylene conversion rate during the acetylene hydrochlorination process.
[0074] Table 1 Catalyst types disclosed in the published literature and the main characteristic parameters of the acetylene hydrochlorination reaction process
[0075]
[0076]
[0077] 3) Performance testing of single, double, and triple-component catalysts:
[0078] Figure 2 Figures 3a and 3b show the results of the catalytic performance tests of single-component (Au / AC, P / AC, Cu / AC), double-component (AuP 14 / AC, Cu 24 P 16 / AC), and triple-component (AuCu 24 P 16 / AC) catalyst compositions. As can be seen from Figure 3a, the overall catalytic performance of the single-component catalysts (Au / AC, P / AC, Cu / AC) and the double-component catalysts (AuP Figure 2 / AC, Cu 14 / AC, Cu 24 P 16 / AC) is inferior to that of the triple-component catalyst AuCu 24 P 16 / AC. Therefore, the present invention has successfully improved the performance and stability of the catalyst through a synergistic electronic modulation strategy. Specifically, among the single-component catalysts, only Au / AC has significant catalytic activity, while the performance of Cu / AC and P / AC is almost negligible, indicating that the Au element is likely the active center of these catalysts. The synergistic effects generated between the catalyst components are not the same. Different from AuCu 24 / AC and AuP 16 / AC, the latter has achieved improvements in both performance and stability, while the former has more significantly enhanced the catalyst performance but caused a decrease in stability, and the overall performance is inferior to that of the triple-component catalyst AuCu 24 P 16 / AC.
[0079] Figure 2 Figure 3b shows the acetylene conversion rates of catalysts with different components, and this data can reflect the selectivity of the catalyst for vinyl chloride monomer (VCM). Among them, the VCM selectivities of the P / AC, Cu 24 P 16 / AC, and Cu / AC catalysts are all lower than 99%, and the VCM selectivities of all catalysts containing the Au component are higher than 99%, once again proving that the Au element is the active center of the catalyst, that is, the AuCu 24 P 16In the AuCuP / AC three-component catalyst, Au is located at the coordination center formed by Cu and P.
[0080] Thermogravimetric comparison test of the catalyst before and after the reaction in Example 3
[0081] The first step of the catalytic reaction with a carbon-containing compound as the raw material is usually adsorption on the catalyst surface to form carbon-containing elements. For example, through decomposition, polymerization and other reactions of the carbon-containing elements, carbon or coke is generated and deposited on the catalyst surface, that is, carbon deposition or coking. Carbon deposition will block the active sites or pores of the catalyst, resulting in the inactivation of the catalyst. Therefore, the amount of carbon deposition is an important indicator to test the stability of the catalyst.
[0082] Thermogravimetric comparative analysis (TGA) of the catalyst before and after the reaction was used to determine the change in carbon deposition caused by the catalyst reaction. From Figure 3 the results shown, the carbon deposition amounts of Au / AC( Figure 3 a), AuCu 24 / AC( Figure 3 b) and AuCu 24 P 16 / AC( Figure 3 c) catalysts reached 1.26 wt.%, 0.69 wt.% and 0.38 wt.% respectively after 24 hours of reaction. It can be seen that the AuCu 24 P 16 / AC catalyst of the present invention has the lowest carbon deposition amount. This may be because the introduction of copper and phosphorus in the catalyst, the synergistic electronic modulation of CuCl2 and iPr2PCl inhibits the generation of carbon deposition during the catalytic process, which helps to maintain the stability of the AuCu 24 P 16 / AC catalyst (especially the carbon deposition amount of AuCu 24 P 16 / AC is reduced to 30.2% of Au / AC), verifying that the three-component catalyst AuCu 24 P 16 / AC provided by the present invention has the characteristic of high stability.
[0083] Morphology and structure analysis of the catalyst before and after the reaction in Example 4
[0084] The morphology and structure of the catalyst before and after the reaction are as shown in Figure 4 and Figure 5 shown, where Figure 4 a, 4b are transmission electron microscope images (TEM) of the Au / AC catalyst before (a) and after (b) the reaction; Figure 4 c is the selected area electron diffraction (SAED) pattern of the Au / AC catalyst after the reaction (c); Figure 4d-4g is the energy-dispersive X-ray spectroscopy (EDS mapping) of the Au / AC catalyst before (4d, 4e) and after (4f, 4g) the reaction. Figure 4 h, 4i are AuCu 24 TEM images of the AuCu / AC catalyst before (h) and after (i) the reaction; Figure 4 j is the selected area electron diffraction (SAED) pattern of the AuCu / AC catalyst after the reaction (j); 24 Figure 4 k - 4p are the energy-dispersive X-ray spectroscopy (EDS mapping) of the AuCu / AC catalyst before (4k, 4l, 4m) and after (4n, 4o, 4p) the reaction, respectively. 24
[0085]
[0086] From the results in Figure 4, it can be seen that after the reaction, agglomerates of the Au element in the catalyst appear in both the Au / AC and AuCu / AC catalysts. The TEM image can clearly show the nanoparticles, and the EDS mapping and SAED spectra fully confirm that the nanoparticles are gold nanoparticles. Moreover, the size of the nanoparticles in the AuCu / AC catalyst after the reaction is significantly lower than that in the Au / AC catalyst, and the nanoparticles appear to be more dispersed, which fully indicates that the addition of copper elements helps the dispersion of gold and inhibits the agglomeration of gold. In addition, the addition of phosphorus further inhibits the agglomeration of metal components. 24 24 24 16
[0086] From Figure 5 a and 5c, it can be seen that in the AuCuP / AC catalyst, before and after the reaction, the catalytic active components are uniformly distributed and no nanoparticles appear, which indicates that the dual regulation of copper and phosphorus fully realizes the uniform dispersion of the AuCuP / AC catalyst and inhibits the agglomeration of the active components, contributing to the maintenance of the stability of the catalyst. 5b and 5d prove that the effective components on the catalyst surface are uniformly distributed and there is no metal agglomeration and ligand decomposition. 24 P 16 24 16 P 31
[0087] Confirmation of the pincer structure of the catalyst in Example 5
[0088] Figure 6 As can be seen from Example 2, there are interactions between both Au - Cu and Au - P. Therefore, it is necessary to confirm the interaction relationship among the three components of the AuCuP / AC catalyst. 24 P 16 31 Figure 6 From the results of the 31P NMR test (as Figure 6As shown in the figure, by comparing the nuclear magnetic resonance (NMR) spectra of iPr2PCl, iPr2PCl + HAuCl4, iPr2PCl + CuCl2, and iPr2PCl + CuCl2 + HAuCl4, it can be seen that the peak positions of the iPr2PCl + CuCl2 + HAuCl4 sample are very close to those of iPr2PCl + HAuCl4, indicating that in the iPr2PCl + CuCl2 + HAuCl4 sample, the Au-P interaction is prior to the Cu-P interaction, that is, the catalyst presents a structure with Au as the center and Cu and P serving as the structural arms of the catalyst respectively, forming a pincer structure. This structure can ensure that the Au element is fully regulated, thus achieving high-performance catalysis for acetylene hydrochlorination.
[0089] In summary, the catalyst for acetylene hydrochlorination reaction and its preparation method provided by the present invention are a low-gold-loading, high-activity, and high-stability acetylene hydrochlorination catalyst. By the synergistic coordination of copper and phosphorus to regulate the electronic state of gold, the aggregation of gold and carbon deposition are inhibited, and the industrial application cost is reduced. Microscopically, the catalyst provided by the present invention constructs a (pincer) coordination center structure at the Au site, and electrons oscillate rapidly in the structure during the catalytic process to complete efficient catalysis. This electronic oscillation can rapidly modulate the electron density of the Au site, meet the different requirements for the stepwise adsorption and catalysis of acetylene and hydrogen chloride, and directly achieve an ultra-low loading of Au and a huge improvement in catalytic performance.
[0090] The specific embodiments described above have further elaborated on the purpose, technical solutions, and beneficial effects of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not used to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A catalyst, comprising an active component, characterized in that, The active components include Au, Cu, and P; among them, Au atoms are located at the coordination center formed by Cu atoms and P atoms.
2. The catalyst according to claim 1, characterized in that, The weight percentage of Au is 0.1% - 0.2%, the molar ratio of Cu to Au is (0 - 30):1, and the molar ratio of P to Au is (0 - 20):
1.
3. The catalyst according to claim 1, characterized in that, The catalyst further includes a catalyst carrier, and the catalyst carrier includes activated carbon.
4. The preparation method of the catalyst according to any one of claims 1-3, characterized in that, It includes the following steps: Step 1: Dissolve HAuCl4, CuCl2, and iPr2PCl in isopropanol to form a precursor solution. Step 2: Immerse the precursor solution in the activated carbon carrier and let it stand. Step 3: Dry at a temperature of 120 - 150 °C to obtain the catalyst.
5. The preparation method according to claim 4, wherein In Step 2, the temperature for standing is 70 - 80 °C, and the time is 2 - 4 h.
6. The preparation method according to claim 4, characterized in that, In Step 3, the drying time is 6 - 12 h.
7. The preparation method of the catalyst according to any one of claims 1-3, characterized in that, It includes the following steps: Step 1: Dissolve HAuCl4, CuCl2, and iPr2PCl in isopropanol to form a precursor solution. Step 2: Immerse the precursor solution in the activated carbon carrier and let it stand at 70 - 80 °C for 2 - 4 h. Step 3: Dry at a temperature of 120 - 150 °C for 6 - 12 h to obtain the catalyst.
8. A method for the hydrochlorination reaction of acetylene, characterized in that, It includes the following steps: Contact the raw materials containing acetylene and hydrogen chloride with the catalyst and react to prepare vinyl chloride. The catalyst is selected from at least one of the catalysts described in any one of Claims 1 - 3 and the catalysts prepared by the preparation method described in any one of Claims 4 - 7.
9. The method according to claim 8, characterized in that, The space velocity of acetylene in the reaction is 300-1080 h -1 , and the reaction temperature is 160-200 °C.
10. The method according to claim 8, characterized in that, The volume ratio of the raw materials of hydrogen chloride and acetylene is (1.1 - 1.3):1.